2013
DOI: 10.1002/rcm.6486
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of SLAP2 and GISP δ17O and proposed VSMOW‐SLAP normalization for δ17O and 17Oexcess

Abstract: The data generated here and compiled from previous studies provide a substantial volume of evidence to evaluate the various normalization techniques currently used for triple oxygen isotope measurements. We recommend that reported δ(17) O and (17)O(excess) values be normalized to the VSMOW-SLAP scale, using a definition of SLAP such that its (17)O(excess) is exactly zero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(142 citation statements)
references
References 26 publications
(122 reference statements)
6
135
1
Order By: Relevance
“…The complexity of the observed spatial distribution suggests that the spatial distribution of 17 O-excess in present-day Antarctic surface snow cannot be simply explained by the moisture source location and its relative humidity, nor by a temperature-dependent supersaturation effect only. Our conclusion is not in agreement with more recent study by Schoenemann et al (2014) who concluded that kinetic isotope effects resulting from supersaturation of water vapor over ice dominate the spatial pattern of modern 17 O-excess in Antarctic precipitation. It is expected that the spatial variability of 17 O-excess in Antarctica should be governed by both the initial 17 O-excess value in vapor over the moisture source region and the supersaturation effect at the precipitation site.…”
Section: Spatial Variabilitycontrasting
confidence: 81%
See 1 more Smart Citation
“…The complexity of the observed spatial distribution suggests that the spatial distribution of 17 O-excess in present-day Antarctic surface snow cannot be simply explained by the moisture source location and its relative humidity, nor by a temperature-dependent supersaturation effect only. Our conclusion is not in agreement with more recent study by Schoenemann et al (2014) who concluded that kinetic isotope effects resulting from supersaturation of water vapor over ice dominate the spatial pattern of modern 17 O-excess in Antarctic precipitation. It is expected that the spatial variability of 17 O-excess in Antarctica should be governed by both the initial 17 O-excess value in vapor over the moisture source region and the supersaturation effect at the precipitation site.…”
Section: Spatial Variabilitycontrasting
confidence: 81%
“…In the case of the transect from the coast to Dome A, our sensitivity tests to different values of q show a reasonable fit with our dataset when using the supersaturation function as S = 1 − 0.0033T c . It is noted that S determined here is the same as the one found for the same MCIM model by Winkler et al (2012) based on the δ 18 O, 17 O-excess and d-excess on the transect from Terra Nova Bay to Dome C and the mean ice-core isotopic values of early Holocene at Vostok, Dome C and Talos Dome; it is lower than the value tested by Schoenemann et al (2014).…”
Section: Comparison Of Mcim Simulations With Our Traverse Datamentioning
confidence: 86%
“…For comparison, the collected average of 5 previously reported IRMS measurements of δ 17 O VSMOW-SLAP in GISP was −13.12 ± 0.06 ‰ (1σ). 13 Allan deviation analyses 30 (not shown) for both δ 18 O and δ 17 O show that averaging improves the precision of the measurements to an instrumental noise floor of approximately 0.02 ‰ in δ 18 O and 0.01 ‰ in δ 17 O. This precision is achieved by averaging 20 HT measurements to produce a single high-precision (HP) measurement as described below.…”
Section: Resultsmentioning
confidence: 99%
“…The 17 O-excess VSMOW-SLAP values for both VSMOW2 and SLAP2 were taken to be defined as zero and thus considered to have no uncertainty for propagation of errors. 13 The uncertainty of the δ 17 O VSMOW-SLAP of SLAP2 was calculated from the uncertainty of δ 18 O VSMOW-SLAP and 17 O-excess VSMOW-SLAP and determined to be 0.02 ‰. In all cases, the uncertainties of the measured δ 18 O and δ 17 O values have been convolved with the uncertainties of the reported VMSMOW2 and SLAP2 values to report values on the VSMOW-SLAP scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation